Comparison of techniques used for functional evaluation of pelvic floor muscles - Christiane Kelen Lucena da Costa; Maria Helena Constantino Spirydes; Maria Bernardete Cordeiro de Sousa (Revista Brasileira em Promoção da Saúde, 2017)
Objective: To identify and discuss techniques for evaluation of pelvic floor muscles (PFM) focusing on the most used and accessible techniques in health care. Methods: This is a quantitative exploratory and descriptive applied research. Data were collected from March to June 2016 at a higher education institution in the city of João Pessoa, Paraíba, Brazil. Initially, 31 healthy young women were submitted to pelvic floor evaluation using the following methods: PERFECT, vaginal cones, and perineometry using Perine and Peritron. The participants then performed exercises to strengthen PFM. The variables measured by the different methods were also recorded 30 and 60 days after the start of the program. ANOVA was used for repeated measures and Spearman's correlation test was used for the evaluation instruments with significance set at 5%. Results: The functional evaluation using all the methods was adequate in the PFM evaluation. In the digital palpation (PERFECT), the endurance response (E) was positively correlated to Perina (rho=0.688) and vaginal cones (rho=0.571), and muscle strength (P) was positively correlated to the Peritron technique (rho=0.506). Conclusion: There are several ways to evaluate PFM function and all of them provide sensory feedback to the patient. Given the low costs of digital palpation, the introduction of this technique into women's health services is likely to improve women's quality of life.